2021
DOI: 10.3847/1538-4357/abfe5e
|View full text |Cite
|
Sign up to set email alerts
|

Kilonova Emission from Black Hole–Neutron Star Mergers. II. Luminosity Function and Implications for Target-of-opportunity Observations of Gravitational-wave Triggers and Blind Searches

Abstract: We present detailed simulations of the kilonova and gamma-ray burst (GRB) afterglow and kilonova luminosity function from black hole–neutron star (BH–NS) mergers, and discuss the detectability of an electromagnetic (EM) counterpart in connection with gravitational wave (GW) detections, GW-triggered target-of-opportunity observations, and time-domain blind searches. The predicted absolute magnitude of BH–NS kilonovae at 0.5 days after the merger falls in the range [−10, −15.5]. The simulated luminosity function… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 269 publications
0
42
0
Order By: Relevance
“…We note that NSBH mergers may have a lower event rate density, that NSBH kilonovae may be dimmer than BNS kilonovae (e.g., Zhu et al 2020) and that most NSBH mergers in the universe are likely plunging events (e.g., Abbott et al 2021a;Zappa et al 2019;Drozda et al 2020;Zhu et al 2021c;Broekgaarden et al 2021). As a result, the detection rates of kilonova and afterglow emissions from NSBH mergers should be much lower than those from BNS mergers (Zhu et al 2021f). In the following calculations, we only consider kilonova and afterglow emissions from BNS mergers.…”
Section: Introductionmentioning
confidence: 98%
“…We note that NSBH mergers may have a lower event rate density, that NSBH kilonovae may be dimmer than BNS kilonovae (e.g., Zhu et al 2020) and that most NSBH mergers in the universe are likely plunging events (e.g., Abbott et al 2021a;Zappa et al 2019;Drozda et al 2020;Zhu et al 2021c;Broekgaarden et al 2021). As a result, the detection rates of kilonova and afterglow emissions from NSBH mergers should be much lower than those from BNS mergers (Zhu et al 2021f). In the following calculations, we only consider kilonova and afterglow emissions from BNS mergers.…”
Section: Introductionmentioning
confidence: 98%
“…Besides, the possible additional energy injection from the remnant BH via fall-back accretion (Rosswog 2007) or the Blandford-Payne mechanism (Ma et al 2018), or from a long-lived NS through magnetic spindown (Yu et al 2013;Metzger & Piro 2014) may enhance the brightness of the kilonova. Because the BNS kilonova emission may display significant diversity and NSBH kilonovae will also contribute to the kilonova magnitude distribution (Zhu et al 2021f), it is expected that cosmological kilonova luminosity function should be more complicated than our simulation result. We also showed that the afterglows have a wider magnitude distribution compared with kilonovae.…”
Section: Discussionmentioning
confidence: 75%
“…Sun et al (2015) suggested the lognormal delay model is one of the favoured delay time model to explain the observations of sGRBs. Hereafter, we adopt the log-normal delay model as our merger delay model whose analytical fitting expression of f (z) is adopted as Equation (A8) of Zhu et al (2021f).…”
Section: Redshift Distributionmentioning
confidence: 99%
“…This scenario would lead to a group of NSBH mergers with a unique spin distribution, which has not been discovered by present GW detections. Zhu et al (2021e) further found that the brightness of kilonova is strongly dependent on the spin magnitude of the BH in the NSBH mergers. The possible energy injection from BH-torus would also be affected by the primary BH spin (e.g., Ma et al 2018;Qi et al 2021).…”
Section: Implications For the Formation Channelmentioning
confidence: 88%
“…where P det is the probability that a NSBH event can be detected. χ eff and χ p have less influence on the detection probability of a NSBH event (e.g., Zhu et al 2021e) so that we ignore the effect of them on the detection probability. We then simulate P det (m 1 , m 2 ) based on the method introduced in Abbott et al (2021c).…”
Section: Hierarchical Population Modelmentioning
confidence: 99%